Bank Management between Shareholders and Regulators - Christian Harm (SUERF - The European Money and Finance Forum, 2002)
This essay discusses the corporate governance of banks. Bank managers must balance competing demands from shareholders and regulators, which distinguishes banks from most other firms. The essay is structured into three parts. The theoretical section first broadly defines management and its governance as a process with certain built-in ambiguities that defy a strict notion of accountability. Then, a focus on financial stakeholders clarifies the different governance objectives of owners and creditors, and integrates bank regulation into the concept of debt governance. The empirical section surveys the extant literature to derive insights as to which theoretical predictions have so far received more wide-spread support, and in which areas the insights generated by researchers may still be too vague to lend themselves as a basis for policy advice. The third section then spells out a recommendation for a logically consistent regime in which shareholders (equity governance) and regulators (debt governance) can meaningfully coexist in their quest to guide and constrain bank managers.
Keywords: G21; G28; G34; 330; banks; bank regulation; corporate governance; Bankmanagement; Corporate Governance; Aktionäre; Bankenaufsicht